PERSONALITY-ORIENTED TECHNOLOGIES FOR UNIVERSITY TEACHERS’ QUALIFICATION RAISING SYSTEM - Elena Yu. Sysoeva (Высшее образование в России)
The article analyzes thepsychological problems of theprofessional development of higher school teachers. The author substantiates the need in applying person2oriented technologies in teachers’ skill upgrading system. The author examines the teaching studio and art therapy techniques as a specific means of training and professional development of university teachers.